Cerebral paradoxical embolism associated with patent foramen ovale and idiopathic venous thromboembolism in a 31-year-old patient - Timnou Bekouti, Jean; Ravakiniaina Ranaivosoa, Mialy; Adossou, Akuvi Claude; Dawara, Alpha; Camara, Ansoumane; Rambolarimanana, Manitrahasina; Lawani, Pierre; Ranjatson, Alain; HOUEZE, Richard; Roynard, Jean Louis (My University, 2020)
Paradoxical embolism is the passage of venous thrombi into the arterial circulation through a pulmonary or intracardiac shunt. We report the management of a 31-year-old patient who initially presented with chest pain and right brachiofacial paresis. A diagnosis of paradoxical cerebral embolism associated with a spontaneous venous thromboembolism and a patent foramen oval was made. The patient benefited from thrombolytic therapy and lifelong anticoagulation with good recovery. This case showed that percutaneous closure of a patent foramen oval needs to be discussed individually.
Keywords: Cerebral paradoxal embolism - Foramen Oval - Idiopathic venous thromboembolism